The Role of Personality Factors in Predicting Migraine Symptoms in Nurses - M Bayrami; M Movahedi; Y Movahedi; A Azizi; A Rahimi (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: Considering the role of personality factors in the etiology of migraine headache as the most common neurological symptoms and medical complaints, this study aimed to determine the association between migraine symptoms and personality factors in nurses.   Martial & Methods: It was a descriptive correlational study. The study population consisted of all female nurses working in educational hospitals of Khorramabad, among them 180 were recruited through Cochran formula using stratified random sampling method. Data was collected by Inventory of Personality factors NEO and Najarian Migraine symptom questionnaires. The criterion validity and reliability of the NEO Personality Inventory was 0/66 and 0/78 respectively, and reliability of migraine questionnaire was 0/80. Data was analyzed by descriptive statistics including mean and standard deviation and also inferential statistics including correlation coefficient and regression analysis using SPSS-PC (v.16).   Results: A significant correlation was found between Personality factors and symptoms of migraine headaches. Multiple regression showed that personality factors explain 42 percent of the variance of migraine headaches in nurses (P< %5).  Conclusion: Considering the predictability of migraine headache by personality factors, the findings could be used as a basis for further research and preventive interventions for nurses with migraine.   Received: 21 Jul 2013   Accepted: 21 Oct 2013